Education and science: current trends - Bodrov A. G., Nikishina A. A., Novikov I. A., Novikov A. P., Surkova G. V., Petrova D. D., Samostroenko G. M., Shatokhina O. V., Cherkashin I. S., Kapustina N. V., Rustamova I. T., Savenkov D. L., Veselova N. I., Grigorian S. S., Milioshina N. A., Firsova I. A., Chibilyova V. P., Chibiliov A. A., Sagitova V. R., Borovkova V. A., Borovkova V. A., Shevtsov V. V., Efremov A. Y., Diakieva B. B., Averianova E. V., Belonovskaia I. D., Sorokina O. A., Rakhimova O. N., Emelianova E. V., Chereshneva I. E., Kokhanova L. A., Golovko S. B., Khokhrina I. S., Khachev M. M., Temmoeva S. A., Cherkasova O. A., Zakirov R. S., Belousova rimma iurevna R. I., Novoselova A. N., Podoplelova N. M., Danilchenko S. L., Boldyrikhina V. N. (Education and science: current trends, 2018)
effective activity of each university is impossible without taking into account its specifics and individual features. In this regard, in each educational institution there is a need to develop and apply additional competencies, and accordingly their own work programs, pedagogical innovations, methodological and didactic materials on academic disciplines in addition to the competencies specified in the Federal State educational Standards of Higher Education that meet the requirements of the competence approach. Such concretization taking into account regional, mental, personal features both of teachers and students is inevitable. Therefore, some opportunity to maneuver is necessary, making something of their own, individual by each university, each individual teacher in the education process. In KBSAU named after V.M. Kokov the pointed out work is carried out within the framework of special professional competences. The authors of the monograph tried to justify the necessity and usefulness of such competencies usage, to show how their use affected the disclosure of personal qualities of students, the development of their abilities for independent work, the creation of new models of lectures and classroom trainings at the university, presented methodological approaches to the organization, conduct and evaluation of extracurricular work.
Keywords: интерактивные технологии; компетентностный подход; competence approach; образовательные программы; educational programs; специальные профессиональные компетенции; математические дисциплины; инновационное обучение; special professional competences; mathematical disciplines; interactive technologies; innovative training